Architecture and Implementation of Fading Compensation for Dynamic Spectrum Access Wireless Communication Systems. (6th June 2013) - Hatanaka, Masahide; Homemoto, Toru; Onoye, Takao
Abstract : This paper proposes an efficient architecture and implementation of fading compensation dedicated to dynamic spectrum access (DSA) wireless communication. Since pilot subcarrier arrangements are adaptively determined in wireless communication systems with DSA, the proposed architecture employs piecewise linear interpolation to the channel response estimation for data subcarriers in order to increase the channel estimation accuracy. The fading compensation for an orthogonal frequency-division multiplexing (OFDM) symbol is performed within the time for one OFDM symbol to make increase of latency smaller. The proposed architecture guarantees real-time processing with 76 MHz or higher clock frequency. The FPGA implementation of the proposed architecture occupies 1, 577 slices and works up to 121 MHz.